PENGARUH GREEN MARKETING DAN PACKAGING TERHADAP BRAND IMAGE DAN LOYALITAS PELANGGAN PADA KONSUMEN STARBUCKS COFFEE - Widya Sari, I Gusti Ayu; Setiawan, Putu Yudi (E-Jurnal Manajemen, 2017)
The purpose of this research was to  determine the effect of green marketing  and packaging towards brand image and customers loyalty at Starbucks Coffee in Bali. The location of this reseach were in Bali with the sample about 104 respondents, using current methods of purposive sampling and incidental sampling. The collection of data obtained from the questionnaire using Likert scale used to measure 13 indicators. This research techniques using path analysis, with a confirmatory test and classical assumption test. The results showed that green marketing and packaging positively and significantly affect the brand image. Green marketing and packaging  significantly positively affect customer loyalty funds with brand image positively and significantly affect customer loyalty. Green marketing has the most direct influence on brand image and customer loyalty. This indicates that green marketing is taking an important role in creating the Starbucks Coffee brand image and increase customer loyalty at Starbucks Coffee in Bali.
Keywords: green marketing, packaging, brand image, customers loyalty